Vestibular prepulse inhibition of the human blink reflex - Ciocca, Matteo; Hosli, Sarah; Hadi, Zaeem; Mahmud, Mohammad; Tai, Yen F; Seemungal, Barry M (Clinical neurophysiology, 2024)
•This is the first report of a vestibular prepulse inhibition of the blink reflex.•A vestibular prepulse inhibits the R2 and R2c area in healthy subjects but not in patients with bilateral peripheral vestibular failure.•Vestibular PPI is a potential neurophysiological marker of vestibulo-motor integration at the brainstem level. Auditory and somatosensory prepulses are commonly used to assess prepulse inhibition (PPI). The effect of a vestibular prepulse upon blink reflex excitability has not been hitherto assessed. Twenty-two healthy subjects and two patients with bilateral peripheral vestibular failure took part in the study. Whole body yaw rotation in the dark provided a vestibular inertial prepulse. Blink reflex was electrically evoked after the end of the rotation. The amplitude of R1 and the area-under-the-curve (area) of the blink reflex R2 and R2c responses were recorded and analysed. A vestibular prepulse inhibited the R2 (p < 0.001) and R2c area (p < 0.05). Increasing the angular acceleration did not increase the R2 and R2c inhibition (p > 0.05). Voluntary suppression of the vestibulo-ocular reflex did not affect the magnitude of inhibition (p > 0.05). Patients with peripheral vestibular failure did not show any inhibition. Our data support a vestibular gating mechanism in humans. The main brainstem nucleus mediating PPI – the pedunculopontine nucleus (PPN) – is heavily vestibular responsive, which is consistent with our findings of a vestibular-mediated PPI. Our technique may be used to interrogate the fidelity of brain circuits mediating vestibular-related PPN functions. Given the PPN’s importance in human postural control, our technique may also provide a neurophysiological biomarker of balance.